Maxillofacial infections in a tertiary hospital in São Paulo, Brazil - A two-year retrospective study - Silva, Vinícius Teixeira; de-Campos, Wladimir Gushiken; de-Souza, Daniel Falbo Martins; da-Fonseca, Eduardo Vasques; Marin, Marco Aurélio Tavelin (Journal of Oral Diagnosis, 2023)
Background: Odontogenic infections can cause fatal complications and should be diagnosed and treated as early as possible, in addition to public health measures for preventing these diseases. Objective: This study aimed to conduct an epidemiological survey of patients hospitalized for odontogenic infections at the Mandaqui Hospital (São Paulo, Brazil) be-tween 02/01/2011 and 02/01/2013. Results: The leading cause of maxillofacial infections was odontogenic, corresponding to 89%. The prevalence of odontogenic infections was higher in males (56%), with a predominance in the age group of 21 to 30 years (36%), with teeth affected by cavities with pulp necrosis being the main responsible for triggering this disease, corresponding to 79%. of cases. The average hospitalization period was 5.31 days. The primary surgical treatment was drainage under general anesthesia associated with immediate extraction in 35% of patients. Conclusions: The primary surgical treat-ment was drainage associated with immediate teeth extraction under general anesthesia, which improved most patients effectively, with few complications reported. This finding reinforces the idea that surgical drainage is the main procedure that leads to the patient’s clinical improvement regardless of the type of antibiotic used.